Perlindungan Negara Terhadap Hak Kebebasan Beragama: Perspektif Islam dan Hak Asasi Manusia Universal - Frans Sayogie (Jurnal Hukum PRIORIS, 2013)
The implementation of religious freedom in Islam still has unresolved issues. Based on the perspective of the Madinah Charter, Islam can provide protection of freedom of religion and give the rights of non-Muslims. Nowadays, however, in practice, in some Islamic countries, there is actually a variety of aberrations that obscures the meaning and spirit of the Madinah Charter. In some Muslim countries, the formalization and formulation of syariah are still implemented in the publicsphere. State does not remain neutral toward all religious doctrines and always strives to apply the principles of syariah as a policy or state legislation. This is also reflected in the Cairo Declaration that gives legitimacy to Muslim countries to maintain and run a syariah-based doctrine that emphasizes the protection of religion rather than the protection of the fundamental rights of freedom of religion.Therefore, the need for the doctrine of separation of religion and state is intended to make state more independent and is expected to provide protection of the organs and institutions of the state against the abuse of power in the name of religion. Right to freedom of religion can only be realized within the framework of the constitutional and democratic state based on the spirit of universal human rights.Key words: right to freedom of religion, state protection, universal human rights